Reinterpretation of the Marriage Age Limit in Islamic Families: Efforts to Prevent Early Marriage as a Family Benefit in Indonesia - Abdurahman, Tubagus (Yayasan Mentari Madani, 2026)
This study analyzes the interfaith marriage controversy in Indonesia through a juridical approach and a contemporary Islamic legal perspective. The unclear norms in Law Number 1 of 1974 concerning Marriage have led to various interpretations and practices in the registration and determination of interfaith marriages by judicial institutions. Meanwhile, Islamic law generally rejects interfaith marriage, especially to preserve faith, descent, and family resilience, although contemporary scholars provide a more contextual interpretation. This research uses qualitative methods through literature studies, interviews, and document analysis. The results of the study show that the disharmonization of regulations creates legal uncertainty and increases requests for determination in district courts. The analysis of maqāṣid al-syarī'ah provides a theoretical basis that the prohibition of interfaith marriage serves to protect the interests of the family and society. This study recommends the need for regulatory harmonization, improving community legal literacy, and an interdisciplinary approach in formulating policies.